The Italian Banking System (1982)
This book describes the institutional framework of the Italian banking system and discusses the bank's role and operations. The aim is to provide basic information only: for this reason, the treatment of each topic is necessarily brief and the reader seeking more details is referred to the extensive literature which can easily be found on all the subjects dealt with in these pages.
Bibliography: p. vii.
osc 20/7/17
Loans
Keywords: Banks and Banking